Giant abdominal aortic aneurysms - Joshua I. Ng, BSE; Tuong Nguyen, MD; Anand Tarpara, MD; Dawn Salvatore, MD, FACS; Paul DiMuzio, MD, FACS; Babak Abai, MD, FACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
Giant abdominal aortic aneurysms (AAAs) are defined as AAAs >10 to 13 cm in the maximum transverse diameter. We have described a case of a patient who had presented for open repair of an 18-cm AAA and a review of reported cases of giant AAAs >10 cm in the maximum transverse diameter. Forty cases were compiled. The average maximum AAA diameter was 14.5 ± 4.1 cm. The AAA was ruptured on presentation in 12 patients (30%). Of the 40 cases, 34 (85%) were repaired with open surgery. The reported mortality was 15%. Despite the case complexity, five endovascular repairs were attempted.